Carbon nanotubes as a unique agent to fabricate nanoceramic/metal composite powders for additive manufacturing. (5th January 2018) - Zhou, Weiwei; Sun, Xiaohao; Kikuchi, Keiko; Nomura, Naoyuki; Yoshimi, Kyosuke; Kawasaki, Akira
Highlights: A novel application of CNTs was exploited for preparing nanoceramic/metal powders. The composite powders kept similar in shape, particle size, and distribution to raw metallic ones. The Al2 O3 -coated metallic powders showed higher laser absorptivity than uncoated ones. Al2 O3 particles were uniformly dispersed and intimately contacted with the matrix after PBF. Graphical abstract: Abstract: Laser powder bed fusion (PBF) offers many technological opportunities for producing high-performance composite parts with tailored structures. However, fabrication of suitable composite powders possessing homogenous dispersion, good flowability, suitable particle size and distribution is a prerequisite and main challenge currently faced. In this study, a novel strategy was developed to prepare nanoceramic/metal powders by using acid-treated carbon nanotubes (ATCNTs) as an agent. In detail, a 3 wt% ATCNT/Al2 O3 colloid, in which the negatively-charged ATCNTs were partially covered with positively-charged Al2 O3 nanoparticles under electrostatic attraction, was obtained by heteroagglomeration; subsequently, the uncovered surface areas of ATCNTs were intimately bonded to the positively-charged MoTiAl powders during their mixing. This ATCNT bridging made individual Al2 O3 uniformly wrap on the surface of MoTiAl without aggregation. The Al2 O3 -coated MoTiAl powders remained similar in shape, particle size, and distribution to uncoated ones, simultaneously showing higher laser absorptivity due to an increased surface roughness. The PBF-processed Al2 O3 -ATCNT/MoTiAl composite was dense, in which Al2 O3 nanoparticles were homogenously dispersed and intimately contacted with MoTiAl, giving rise to an increase in the hardness of the matrix.